2015
DOI: 10.1111/ijs.12574
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Carotid Stenosis is Associated with Gray and White Matter Damage

Abstract: Patients with asymptomatic carotid stenosis have different patterns of gray and white matter abnormalities. While the white matter damage is diffuse, the gray matter atrophy is localized in the territory of anterior circulation ipsilateral to the stenosis. The role of asymptomatic carotid stenosis in the gray matter damage must be further investigated with longitudinal studies and comparison with neuropsychological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
3
20
0
2
Order By: Relevance
“…A pilot study suggested, that altered cerebral perfusion in carotid stenosis is associated with regional cortical thinning [12]. Another study revealed a decrease of cortical thickness specifically in the anterior cerebral artery territory [13]. Several studies report an association of carotid artery stenosis with impaired cognitive performance [1422].…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study suggested, that altered cerebral perfusion in carotid stenosis is associated with regional cortical thinning [12]. Another study revealed a decrease of cortical thickness specifically in the anterior cerebral artery territory [13]. Several studies report an association of carotid artery stenosis with impaired cognitive performance [1422].…”
Section: Introductionmentioning
confidence: 99%
“…Our major finding was that patients with ACS had significantly reduced bilateral thalamic volume, particularly in the medial dorsal thalamus. Previous studies have reported global gray matter atrophy in patients with ACS, 7 however, these studies did not investigate (or only marginally investigated) the relationship between subcortical nuclei and cognitive impairment. Consistent with previous, 19,20 the ACS patients in our cohort had a poorer cognitive performance in multiple cognitive domains compared to controls.…”
Section: Discussionmentioning
confidence: 95%
“…6 Previous studies using structural MRI have identified cortical atrophy in patients with ACS. 6,7 Similarly, the atrophy of subcortical nuclei including the thalamus, caudate, putamen, pallidum, hippocampus, amygdala, and nucleus accumbens was also reported in patients with Alzheimer's disease dementia. Moreover, in ACS patients, reduced cerebral blood flow 8 and decreased vascular reactivity 9 of the basal nuclei (caudate, pallidum and thalamus) were reported.…”
Section: Introductionmentioning
confidence: 92%
“…In the classical, instantaneous BCCAo model of chronic cerebral hypoperfusion, the irreversible disruption of the white matter and myelin degradation has been suggested to be responsible for cognitive dysfunction that is correlated with the myelin changes [ 11 , 61 ]. In humans, while the carotid stenosis-related atrophy was lateralized to the side of the stenosis [ 79 ], the white matter disintegration, as measured by diffusion tensor imaging, was found more extensively [ 80 ]. Furthermore, the parallel dynamic changes in cognitive function and in the white matter diffusion parameters after endarterectomy propose white matter microstructural measures as a potential biomarker [ 81 ].…”
Section: Discussionmentioning
confidence: 99%